Ibrutinib Suppresses Early Megakaryopoiesis but Enhances Proplatelet Formation - Huang, Jiansong; Huang, Shujuan; Ma, Zhixin; Lin, Xiangjie; Li, Xia; Huang, Xin; Wang, Jinghan; Ye, Wenle; Li, Yang; He, Daqiang; Yang, Min; Pan, Jiajia; Ling, Qing; Li, Fenglin; Mao, Shihui; Wang, Huafeng; Wang, Yungui; Jin, Jie (Thrombosis and Haemostasis, 2020)
Ibrutinib, an irreversible inhibitor of Bruton's tyrosine kinase, has a favorable safety profile in patients with B cell-related malignancies. A primary adverse effect of ibrutinib is thrombocytopenia in the early stages of treatment, but platelet counts increase or recover as treatment continues. Currently, the effects of ibrutinib on megakaryopoiesis remain unclear. In this study, we investigated the mechanism by which ibrutinib induces thrombocytopenia using cord blood CD34+ hematopoietic stem cells (HSCs), a human megakaryoblastic cell line (SET-2), and C57BL/6 mice. We show that treatment with ibrutinib can suppress CD34+ HSC differentiation into megakaryocytes (MKs) and decrease the number of colony-forming unit-MKs (CFU-MKs). The ibrutinib-dependent inhibition of early megakaryopoiesis seems to mainly involve impaired proliferation of progenitor cells without induction of apoptosis. The effects of ibrutinib on late-stage megakaryopoiesis, in contrast to early-stage megakaryopoiesis, include enhanced MK differentiation, ploidy, and proplatelet formation in CD34+ HSC-derived MKs and SET-2 cells. We also demonstrated that MK adhesion and spreading, but not migration, were inhibited by ibrutinib. Furthermore, we revealed that integrin αIIbβ3 outside-in signaling in MKs was inhibited by ibrutinib. Consistent with previous clinical observations, in C57BL/6 mice treated with ibrutinib, platelet counts decreased by days 2 to 7 and recovered to normal levels by day 15. Together, these results reveal the pathogenesis of ibrutinib-induced transient thrombocytopenia. In conclusion, ibrutinib suppresses early megakaryopoiesis, as evidenced by inhibition of MK progenitor cell proliferation and CFU-MK formation. Ibrutinib enhances MK differentiation, ploidy, and proplatelet formation, while it impairs integrin αIIbβ3 outside-in signaling.
Keywords: ibrutinib; megakaryopoiesis; proplatelet formation; thrombocytopenia